The implementation of a GC/MS data system using DISNET: a Distributed Instrument System NETwork - Gemperline, Paul J.; Megargle, Robert (East Carolina University, 1984)
The primary goal of a computer network is to achieve resource sharing between several computers. Resource sharing is most easily performed at the application program level, with lower layers of software providing communications services. Application programs which make local data, peripherals, or processes available for shared use are defined as ’resource providers’. Application programs which require such resources from the network are defined as ’resource consumers’. This distinction helps the system designer identify the qualities of resource providers and consumers necessary to address data communication problems in a straightforward manner, while ensuring the effort invested will provide satisfactory solutions. We have developed this resource sharing protocol for the Distributed Instrument System NETwork (DISNET) to provide an environment suitable for the development and growth of a distributed system for real-time instrument control, data acquisition, and computation in a laboratory environment.
Keywords: GC/MS; DISNET; Distributed instrument system NETwork; Resource sharing